Influence of Annealing on Warping Angle on Polylactic Acid in Fused Deposition Modeling 3D Printer - Leo Hutri Wicaksono; Akhmad Farid (Widyagama University of Malang, 2023)
The industrial world has been developing at an increasingly rapid pace. The use of additive manufacturing technology is increasingly being used by various companies around the world. Fused deposition modeling (FDM) is a type of 3D printing that falls under the category of material extrusion. It is also known as fused filament fabrication (FFF). Fused deposition modeling (FDM) is the most cost-effective additive manufacturing technique. Polylactic acid (PLA) is a type of plastic that is made from renewable resources such as corn starch, tapioca roots, chips or starch, or sugarcane. It is biodegradable and bioactive and can be used for a variety of applications such as packaging materials, disposable tableware, medical implants, and 3D printing. PLA is also used in the food industry as a food packaging material. The goal of this study is to analyse the warping angle of PLA. In this study, the commercial eSUN PLA filament manufactured by Shenzhen Essun Industrial with a diameter of 1.75 mm was used. This study used experimental method with predetermined conditions such as ISO 527-2 printed specimens, annealing temperature at 50⁰C and 70⁰C. The test result shows that annealing at 50⁰C have the highest degree of side view 1.88⁰, and 1.32⁰ on average. The top view have 2.21 ⁰ and 1.19 on average. Afterwards, the study shows that annealing at 70⁰C have the highest degree of side view 6.19⁰, and 3.96 on average. The top view have 3.84⁰, and 2.33⁰ on average.